Civic Communication and Intercultural Education - Zaleskienė, Irena (Acta Paedagogica Vilnensia, 2006)
The article deals with the theoretical and practical problems of intercultural education. The major goals of the article is to present and analyse the results coming from the international, comparative research on effectiveness of the certain methodology for multicultural education. The concepts of ''civic communication" as well as "'intercultural education" are discussed from sociological and educational perspectives in the first part of the article. And it is shown that civic communication is one of the components of the content and the main actor for intercultural education. The Methodology of the Structured Academic Controversy are presented in the second part of the 61 article as well as the results of the international research on effectiveness of the methodology mentioned above is analysed. The respondents were coming from really multicultural community: 2000 students and 90 teachers from six USA sites and 6 European sites participated in the research (Lithuania, Russia, Czech Republic, Turkmenistan, Estonia, Azerbaijan). Analyses of data did show significant changes in students’ knowledge and understandings of political processes; in students’ attitudes towards presenting different opinions; in students’ behaviours. The results in the article are illustrated by the comments from interviews and focus groups with teachers and students. On the bases the analyses of literature and the results of the research the major conclusions about effectiveness of the methodology of the Structured Academic Controversy are drawn by author of the article. And assumption that civic communication is essential basis for intercultural education.
Keywords: civic communication; multiculturalism; intercultural education